VD_FINDINFO HC / 2013 / 215 vom 4. März 2013 - VD Tribunal cantonal (2013)
HARCÈLEMENT SEXUELDROIT DU TRAVAIL, CONSTATATION DES FAITS, RÉSILIATION IMMÉDIATE, CONTRAT DE TRAVAIL | 321 CO, 328 al. 1 CO, 337 CO, 342 al. 1 CO, 4 LEg, 37 LJT, 16 al. 1 LPers-VD, 61 LPers-VD, 26 al. 1 RCTH, 26 al. 2 RCTH, 3 RCTH